Enhancing Communication among Deaf and Hard of Hearing (DHH) Individuals with Language Learning Apps: Case of 15 DHH in Mostaganem - BENSLIMANE, Cherifa (My University, 2024)
Auditory limitations and the lack of accessible communication channels present distinct obstacles for deaf and hard-of-hearing individuals in their daily activities, mainly in Algeria. Indeed, this issue necessitates exploring innovative solutions. Thus, this research investigates the potential of tailored language learning applications as it aims to explore how these apps can impact deaf people's communication and educational experiences. To conduct our study, our research utilized two primary research tools: online focused group discussions and a targeted questionnaire intended for people who are deaf or hard of hearing living in Mostaganem City, Algeria . The findings revealed that a well designed application can enhance the utility and approachability for the deaf community. Furthermore, the development and integration of tailored language learning a pplications specifically designed for deaf people has the potential to bridge the communication and social gap with hearing family members. These applications could foster stronger relationships by enhancing communication skills. Based on the key findings of this research, we will offer suggestions and recommendations for incorporating even more effective options, ultimately contributing to a deeper level of understanding.
Keywords: DHH; Deaf education; language learning app; Sign language; Deaf communication